Language outcome of very low birth weight babies at 2-year corrected age: A comparative study - Daniel, Reeba Ann; George, Babu (Indian Journal of Child Health, 2019)
Background: Improved survival of preterm infants has resulted in increase in motor and cognitive dysfunctions which have reduced health-related quality of life. Objective: The objective of this study was to assess the receptive and expressive language (EL) development of very low birth weight (VLBW) babies at 2-year corrected age and compare it with normal birth weight (NBW) “at-risk” babies on developmental follow-up. Materials and Methods: This was a cross-sectional study which compared the language outcome which was measured using Receptive-Expressive Emergent Language Scale. Results: The study included 75 VLBW babies and a comparison group of 26 NBW babies. The mean receptive language quotient in VLBW and NBW babies was 91.37±8.35 and 97.19±7.07, respectively (p=0.002). The mean EL quotient in VLBW and NBW babies was 82.64±12.32 and 92.77±10.47, respectively (p